Gathering souls: Jesuit missions and missionaries in Oceania (1668-1945) - Coello de la Rosa, Alexandre (Brill Research Perspectives, 2019)
This essay deals with the missionary work of the Society of Jesus in today's Micronesia from the seventeenth to the twentieth century. Although the Jesuit missionaries wanted to reach Japan and other Pacific islands, such as the Palau and Caroline archipelagos, the crown encouraged them to stay in the Marianas until 1769 (when the Society of Jesus was expelled from the Philippines) to evangelize the native Chamorros as well as to reinforce the Spanish presence on the fringes of the Pacific empire. In 1859, a group of Jesuit missionaries returned to the Philippines, but they never officially set foot on the Marianas during the nineteenth century. It was not until the twentieth century that they went back to Micronesia, taking charge of the mission on the Northern Marianas along with the Caroline and Marshall Islands, thus returning to one of the cradles of Jesuit martyrdom in Oceania